Tumor‐Associated Glycan Exploits Adenosine Receptor 2A Signaling to Facilitate Immune Evasion - Jing‐Yan Cheng; Hsiu‐Hui Tsai; Jung‐Tung Hung; Tsai‐Hsien Hung; Chun‐Cheng Lin; Chien‐Wei Lee; Zi‐Chi Lo; Jing‐Rong Huang; Shih‐Pin Chiou; Yenlin Huang; Shih‐Hsiang Chen; Chun‐Nan Yeh; et al. (Advanced Science)
Abstract Adenosine signaling is a crucial immunosuppressive pathway within the tumor microenvironment, making it a promising target for cancer therapy. In this study, it is demonstrated that Globo H ceramide (GHCer), the most prevalent tumor‐associated glycosphingolipid, influences the tumor microenvironment by activating adenosine signaling, which results in dual immunosuppressive effects on T cells. It is demonstrated that GHCer interacts with the adenosine receptor 2A (A2AR), triggering cyclic AMP (cAMP) and protein kinase A (PKA) signaling. This interaction leads to a reduction in the proliferation of CD4+ T cells while simultaneously promoting the differentiation of regulatory T cells (Tregs). Furthermore, GHCer enhances the suppressive capacity of Treg cells by upregulating inhibitory molecules such as Lymphocyte‐activation gene 3 (LAG3), cytotoxic T‐lymphocyte‐associated protein 4 (CTLA‐4), Programmed cell death 1 ligand 1 (PD‐L1), and it stimulates the secretion of the immunosuppressive cytokine Interleukin 35 (IL‐35). Additionally, GHCer‐induced Tregs express CD39 and CD73, which further enhances adenosine production and creates a positive feedback loop in the adenosinergic pathway and A2AR signaling. Mechanistically, it is found that GHCer forms a complex with TRAX (translin‐associated factor‐X) and the C‐terminus of A2AR, which facilitates the activation of A2AR and promotes an immunosuppressive tumor microenvironment.